Methods of reducing expressions in Arabic (Journal of Oriental Studies, 2018)
This article discusses the use and methods of creating and developing abbreviated words in Arabic.The method of abbreviation of terms in hadith is analyzed, as well as the «naht» method, which waswidely used in the Middle Ages to shorten a few words, phrases and sentences in one word. This articlediscusses the modern problems of abbreviation, which appeared as a result of the development of scienceand technology.